PENGARUH BERBAGAI DOSIS DAN CARA APLIKASI PUPUK UREA TERHADAP PRODUKSI TANAMAN SAWI (Brassica juncea L.) PADA TANAH INCEPTISOL MARELAN - Srie Elvhi Febri Yanti; Erwin Masrul; Hamidah Hannum (Jurnal Agroekoteknologi, 2014)
The application of urea fertilizer which excessive dosage caused the damaged of plant growth. Theobjective of this research was study the accurate dosage and method in application of Urea fertilizerin increasing plant growth of green mustard. The research was conducted in Agriculture Faculty,University of Sumatera Utara, Medan. This research used factorial blocky randomized design with3 block and 2 factors. The dosage of Urea ferlizer (N) were consisted of four kind are : U0 (0 ppmN), U1 (100 ppm N), U2 ( 200 ppm N), and U3 (300 ppm N) and the application method consistedof four levels, namely : D1 (spread) and D2 (mixed). The result of this research showed that somedosages and the way to apply the urea fertilizer did not effect the growth of mustard but effected theproduction of mustard. Highest production was dosage 200 ppm. The application of urea was mixedinto soil better then spread in increase the productivity of mustard. If urea mixed into soil, theoptimum dosages was 117 ppm and if urea spread, the optimum dosages was 190 ppm.Keywords: green mustard, mixed, spread, and urea.